Social research methodology : a critical introduction - Gomm, Roger (Basingstoke [England] : Palgrave MacMillan, 2008)
'The second edition of this popular book continues to support students through each and every step of their research projects. Drawing on a much-praised critical approach, Social Research Methodology 2e helps students to gain a full understanding of social research tools and theory, and explains the methods of putting them into practice.''Introducing and exploring all the key quantitative and qualitative methods, Roger Gomm helps students understand how to choose the right data collection technique to get the results they want. This practical book is invaluable reading for all those studying across education, health and social sciences.'--BOOK JACKET.
Includes bibliographical references (p. 391-417) and index.
Keywords: Social sciences -- Research -- Methodology; Social sciences -- Methodology; Social surveys -- Methodology